Influence of geomorphology and weathering of rocks on soil moisture and water refills in the headwaters of the Jequetepeque river basin - Alcántara Boza, Alejandro (2019)
The present study was developed in the north of Peru, the Jequetepeque River basin, cordillera of the Andes in direction to Pacífico sea. In its main course is the dam Gallito Ciego, source of water for agricultural activity in the coastal of the Jequetepeque valley and electric power generation; however, water deficiencies and lack of knowledge of importance on basin headwaters as an important water contribution, its allow us to study, how geomorphology and weathering influence on soil moisture and water recharge along the headwaters on Jequetepeque river basin. As part of the methodology our generated an integrated system of physical parameters: the geomorphological, the slope, the weathering, the rain, runoff, humidity and vegetation.  The results show that geomorphology is an important variable in humidity; likewise the existence of a strong weathering in northern part of the basin with respect to the southern part, influences the humidity conservation of 33.87% and the generation of a humid forest with aliso plants. Consequently, the humidity and recharge of groundwater is explained by the topography, the weathering of rocks, also arguing that they are the most important events at the northern head of the Jequetepeque River basin.